Inpatient and Emergency Room Ophthalmology Consultations at a Tertiary Care Center - Daniel J. Oh; Levi N. Kanu; Judy L. Chen; Ahmad A. Aref; William F. Mieler; Peter W. MacIntosh (Journal of Ophthalmology)
Background. An ophthalmology consultation service is of significant benefit to patients in the hospital and is an instructive component of a residency education program. Ophthalmology consultations in a hospital present unique challenges to those seen in an outpatient clinic, for which the consulting ophthalmologist should be prepared. The purpose of this study was to profile the emergency room and inpatient ophthalmology consultations seen at an academic institution. Methods. A prospective study of 581 patients was conducted on inpatient and emergency room ophthalmology consultations at the University of Illinois at Chicago over twelve months. Characteristics such as the consulting service, type of and reason for consultation, subspecialty staffing service, diagnosis, and suitability for in-hospital evaluation were recorded. Results. Consultations were received from either inpatient wards (59.4%) or the Emergency Department (40.6%). The most common inpatient consulting services were internal medicine (22%), followed by neurosurgery (16%) and neurology (7%). All the consultations were categorized as acute (72.3%), chronic (6.0%), or screening (21.7%). Consultations categorized as screening included papilledema (31.0%), fungemia (20.6%), syndromic evaluation (19.8%), visual field evaluation (17.5%), and miscellaneous evaluation (11.1%). We classified the ophthalmic diagnoses into 63 unique diagnoses. Amongst the ophthalmic subspecialties, neuro-ophthalmologic diagnoses were the most common (32.0%), followed by retina (20.1%) and cornea (19.4%). Neuro-ophthalmology had the highest proportion of screening consultations (36.6%), while glaucoma had the least overall number of consultations (10.1%), and the least proportion of screening consultations (3.6%). A significant proportion of nonacute consultations (19.0%) was deemed to be more suitable for outpatient evaluation. Discussion. Consultation databases can be useful in preparing trainees for in-hospital clinical care. A wide range of ocular pathologies may present to the ophthalmology consultant, from acute trauma to screening for systemic syndromes. Some consultations may be more suitable for outpatient evaluation which may help optimize patient care.